The Hatfield memorial lectures. - Beeley, Peter R. (Woodhead Publishing series in metals and surface engineering., 2005)
This is the third volume in a series which brings together a selection of the currently available lectures based on broad subject groupings. It focuses on two themes: process metallurgy, including the technical aspects of plant design and operation, and the organisation of the iron and steel industry, including its general structure and economic circumstances. Whilst there is occasional overlap with the themes of Volume 1 (materials properties/behaviour and materials applications) and Volume 2 (metallography and the structure of iron and steels), the current volume compliments the earlier ones and completes the original concept of five themes to bring the anthology up to the present day.